2016
DOI: 10.1016/j.healthplace.2016.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Walkability and cardiometabolic risk factors: Cross-sectional and longitudinal associations from the Multi-Ethnic Study of Atherosclerosis

Abstract: We used data from 3,227 older adults in the Multi-Ethnic Study of Atherosclerosis (2004–2012) to explore cross-sectional and longitudinal associations between walkability and cardiometabolic risk factors. In cross-sectional analyses, linear regression was used to estimate associations of Street Smart Walk Score® with glucose, triglycerides, HDL and LDL cholesterol, systolic and diastolic blood pressure, and waist circumference, while logistic regression was used to estimate associations with odds of metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 65 publications
1
35
0
Order By: Relevance
“…A flowchart of the selection process is presented in figure 1. From the 12 757 identified studies, after screening for relevant titles, abstracts and full manuscripts, 66 articles that fitted the eligibility criteria were selected 30–95. Summary characteristics are shown in table 2 and complete characteristics of the studies are shown in online supplementary file 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A flowchart of the selection process is presented in figure 1. From the 12 757 identified studies, after screening for relevant titles, abstracts and full manuscripts, 66 articles that fitted the eligibility criteria were selected 30–95. Summary characteristics are shown in table 2 and complete characteristics of the studies are shown in online supplementary file 2.…”
Section: Resultsmentioning
confidence: 99%
“…There were several reasons that were provided for not measuring changes in neighbourhood characteristics when two residential location measurements were collected. These reasons included the absence of historical data, such as the Walkscore,40 89 or the availability of data at only one time during the follow-up period, such as through a census or land survey 46 57 75 76…”
Section: Resultsmentioning
confidence: 99%
“…In the absence of self-selection data, alternative analytical approaches (i.e. propensity score matching and fixed effects models) can be used (90) to address confounding due to residential self-selection as was done in some reviewed studies (43,44,46,49,(52)(53)(54)67,68).…”
Section: Residential Self-selectionmentioning
confidence: 99%
“…Walkability impacts residents' leisure-time PAs, transportation choices, and an active lifestyle (41). Poor walkability causes long-term consequences of cardiometabolic diseases (42). In predictive models 2 and 3, only recreational facilities was a signi cant predictor of MVPAs.…”
Section: Discussionmentioning
confidence: 99%